2010
DOI: 10.1186/1471-2407-10-196
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression and single-nucleotide polymorphism profiling discriminates chromophobe renal cell carcinoma and oncocytoma

Abstract: BackgroundChromophobe renal cell carcinoma (chRCC) and renal oncocytoma are two distinct but closely related entities with strong morphologic and genetic similarities. While chRCC is a malignant tumor, oncocytoma is usually regarded as a benign entity. The overlapping characteristics are best explained by a common cellular origin, and the biologic differences between chRCC and oncocytoma are therefore of considerable interest in terms of carcinogenesis, diagnosis and clinical management. Previous studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 28 publications
(32 reference statements)
1
69
1
Order By: Relevance
“…18 Using a combination of gene expression and high throughput SNP platforms, Tan et al generated a probe signature that could discriminate chromophobe RCC and renal oncocytomas. 19 Petillo et al identified a unique miRNA signature for clear cell, papillary, chromophobe RCC and renal oncocytoma. 20 There is growing evidence that not only genetic but also epigenetic changes play important roles in human malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Using a combination of gene expression and high throughput SNP platforms, Tan et al generated a probe signature that could discriminate chromophobe RCC and renal oncocytomas. 19 Petillo et al identified a unique miRNA signature for clear cell, papillary, chromophobe RCC and renal oncocytoma. 20 There is growing evidence that not only genetic but also epigenetic changes play important roles in human malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic inactivation of the VHL TSG is a critical and early event in the pathogenesis of cRCC in VHL disease and in many sporadic cRCC; however, additional genetic and epigenetic events are required for the development of cRCC. Recently high resolution genome wide copy number analysis and high throughput sequencing of candidate genes have been employed to delineate the ''post-VHL inactivation events'' that occur in the development of sporadic RCC (Beroukhim et al, 2009;Dalgliesh et al, 2010;Tan et al, 2010). However, RCC is clinically and histopathologically heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that parafibromin expression was inversely linked to tumor size, pathologic stage, and lymphovascular invasion of breast carcinomas (Selvarajan et al, 2008). Another study showed that parafibromin was a novel immunohistochemical markers effectively discriminating chromophobe renal cell carcinoma and renal oncocytoma (Tan et al, 2010). In our previous work, it was found that down-regulated parafibromin expression might contribute to the pathogenesis, growth, invasion and metastasis and be regarded as a good marker to indicate the poor prognosis of gastric or colorectal carcinoma patients Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%